Exchange Market Pressure in Postwar Brazil: An Application of the Girton-Roper Monetary Model - Connolly, Michael; Silveira, José Dantas da (American Economic Review, 1979)
This study applies Lance Girton and Don Roper's (hereafter G-R) monetary model of market pressure to the postwar Brazilian monetary experience. The model was designed specifically for the Canadian managed float during the period 1952-62. The object of their model is to explain what they term exchange market pressure; that is, the pressure on foreign reserves and the rate when there exists an excess of domestic money supply over money demand in a managed floating rate regime. The basic theoretical proposition is that any such excess supply of money can be relieved by an depreciation, a loss in foreign reserves, or, in the context of a managed float, by some combination of the two. In this sense, the G-R managed float model used here is firmly rooted in the modern monetary approach to rates and the balance of payments.' Brazil provides a particularly good example for testing this approach, not only because it is in many senses a unique example of a postwar managed float system, but also because it can be treated as a small, open economy in the sense that world prices and monetary conditions faced by Brazil are taken as given. This particularly suits the purpose of most modern monetary models which make this assumption and obviates the problems of monetary dependence and neutralization dealt with in the pioneering G-R paper. Specifically, the small-country assumption permits us to devise a simple one-country equation of managed floating which depends upon four essential ingredients: 1) money demand, 2) money supply, 3) purchasing power parity, and 4) monetary equilibrium.2 Furthermore, in Brazil a much greater proportion of market pressure was absorbed by rate depreciation than in the Canadian case where changes in reserves were large relative to rate movements. In short, postwar Brazil provides a singularly good opportunity to test the monetary model of market pressure. Section I briefly states the essential elements of the monetary model, and derives the equation to be tested for the Brazilian experience from 1955 to 1975. Section II reports empirical results for the market pressure model, and Section III examines the applicability of the relative version of purchasing power parity for the time period considered. Section IV summarizes the results and discusses the merits of the monetary approach in light of the Brazilian experience.